Neurological Disorder Case for First-Year Medical Students - Team-Based Learning (TBL) Format - Maria Sheakley; Neils Larsen; Mary Moore; Bruce Wright (Association of American Medical Colleges, 2010)
Abstract This team-based learning (TBL) module encourages learners to work effectively in small groups to discuss and understand the normal anatomy and physiology of a cell, and to be able to describe which abnormal cellular processes produce a specific disease, outlined in the clinical application exercise. The learners will also discuss the anatomy and physiology of nerve transmission, and relate the underlying mechanisms of this to the disease in the application exercise. Finally, learners will determine the inheritance pattern of the disease in the application exercise, and use this for risk calculations while applying the Hardy-Weinberg principle of population genetics. The module follows the basic TBL structure and is written to utilize the "Four S's" in order to foster teamwork and group discussion. This TBL session requires approximately two hours to complete and includes an individual readiness assessment test, a group readiness assessment test, and a group clinical application case. This module allowed first-year students to review several common basic science concepts in a clinical setting. The most effective part of the case was the inclusion of lab data that helped the student to develop their analytical skills to come to some conclusions about the patient, but not necessarily a diagnosis. This stimulated great discussion and helped the students see the relevance of basic science education in the context of medicine. The student feedback from this module was all positive.